Hiscock, Norman Leroy. Interview about life in Champney's West, NL. - Barrett, Terra; Jarvis, Dale (2015)
Interview with Norman Leroy Hiscock of Champney's West, NL about growing up in the community, his work, ship wrecks, local stories, life in Champney's West during World War Two, and stories of local characters. Setting up; 0:47 - Norman Leroy Hiscock was named after his father Norman but was called Roy in order to avoid confusion; Hiscock was born January 9th, 1926 in Freshwater Conception Bay North, NL; 2:10 - Hiscock describes keeping cows for milk and for meat; Hiscock explains how his mother would give food such as potatoes and milk to families in the community who were less fortunate and needed food to eat; 5:28 – Hiscock describes the weekly meals his family would eat growing up; 6:13 – Hiscock describes his family; Description of life as a child; 7:40 - Sister’s work as a teacher; 9:22 – Hiscock describes the school in Champney’s West, the teacher, punishment; 11:34 – Hiscock describes his first job in Badger, NL with the Anglo Newfoundland Development Company; 13:01 – Hiscock describes how the men with the Anglo Newfoundland Development Company worked together to make money for their boss whose wife was sick with cancer; 15:19 – Hiscock describes working with horses as a teamster; 15:50 – Hiscock explains his move to Upper Lake Shipping Company; 17:16 – Hiscock describes a rescue on February 14th, 1942 of three brother Patrick, Earl, George Bannister from Port Rexton; William Noseworthy took rope and tied around his waist and walked across the snow covered ice and tied the rope to the boat and the people hauled in the boat with the three brothers inside; Description of hauling their boat in; 23:17 – Hiscock tells a story of Noseworthy saving another man while working on a Lake Boat and dying in the process; 25:38 – Hiscock tells a funny story about William Noseworthy and his sister Betty; 26:18 – Hiscock tells the story of the Hazel Pearl; Mifflin's saved the boat; The wreck commissioner decided how to share the materials which came from shipwrecks; The people of the community went on board to take ...